2017
DOI: 10.1515/zireb-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Corporative Reporting Designed to Enhance Corporate Governance: Evidence from the Banking Sector in Croatia

Abstract: Abstract:The main objective of this research paper is to examine whether the practice of corporate governance (CG) measured by the CGI-Crobank® index is signifi cant for the explanation of variations in the performance of Croatian banks measured by the return on assets, return on equity, interest margin, margin of non-interest income, operating expenses margin, and by Tobin's Q for the observed period from 2011 to 2015. The research is made on Croatian banks that form the CGI-Crobank® index using the data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the case of Central and Eastern Europe, such evidence is provided by the Bistrova and Lace (2012), who based on a model that included 21 features of corporate governance, concluded that 25% of the companies with the best characteristics of corporate governance significantly exceed performance of 25% of companies at the bottom of the list in terms of attractiveness, investment access and risk management. Similarly, in the case of Croatia, Kokotec, Čalopa and Detelj (2017), in a sample that included a number of companies listed on the Croatian Stock Exchange found a relevance of the best ranking for companies in terms of the corporate governance index for successful business performance.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In the case of Central and Eastern Europe, such evidence is provided by the Bistrova and Lace (2012), who based on a model that included 21 features of corporate governance, concluded that 25% of the companies with the best characteristics of corporate governance significantly exceed performance of 25% of companies at the bottom of the list in terms of attractiveness, investment access and risk management. Similarly, in the case of Croatia, Kokotec, Čalopa and Detelj (2017), in a sample that included a number of companies listed on the Croatian Stock Exchange found a relevance of the best ranking for companies in terms of the corporate governance index for successful business performance.…”
Section: Literature Reviewmentioning
confidence: 95%